Identification of NUDT5 Inhibitors From Approved Drugs - Tong, Xin-Yu; Liao, Xuan; Gao, Min; Lv, Bo-Min; Chen, Xiao-Hui; Chu, Xin-Yi; Zhang, Qing-Ye; Zhang, Hong-Yu (Frontiers in Molecular Biosciences, 2020)
Recent studies have revealed the important role of NUDT5 in estrogen signaling and breast cancer, but research on the corresponding targeted therapy has just started. Drug repositioning strategy can effectively reduce the time and economic consuming in drug discovery. To find novel inhibitors of NUDT5, we investigated the previously identified connectivity map-based drug association models and found eighteen FDA approved drugs as candidates. The molecular docking and molecular dynamic simulation were performed and revealed that fourteen organic drugs have the potential to bind the NUDT5 target. Eight representative drugs were selected to perform the cell line viability inhibition analysis, and the results showed that seven of them were able to suppress MCF-7 breast cancer cells. Two drugs nomifensine and isoconazole showed lower IC50 than the known antiestrogens raloxifene and tamoxifen, and they deserved further pharmacodynamic investigations to test their feasibility for use as NUDT5 inhibitors.